The Implementation of Strikim Media To Improve Student Learning Outcomes in Operations on Integers at Elementary School - Helman Helman (JP2D (Jurnal Penelitian Pendidikan Dasar) UNTAN, 2020)
This research was a classroom action research (CAR) carried out to improve the learning process with the steps of planning, implement, observing, and reflecting. This research was carried out in mathematics by utilizing the media of crime tests on integer count material. The formulation of the problem in this research were: (1) Can the media of crime be able to improve mathematics learning outcomes in integer counts ?; (2) What are the learning outcomes of each cycle by utilizing the learning outcomes of students ?. The results of the study showed that the use of stikrim media in mathematics learning integer count material could improve student learning outcomes. The results of the first cycle test were obtained by six students or 60% complete, and four students or 40% incomplete. Then the results of the second cycle test showed nine students or 91% complete and three students or 10% not complete. The increase occured in students who have reached 88% of students have completed and exceeds 75% indicators of success, and it is stated that the improvement of this learning has been successful.